2008
DOI: 10.1073/pnas.0707260105
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between HMGA1a and the origin recognition complex creates site-specific replication origins

Abstract: In all eukaryotic cells, origins of DNA replication are characterized by the binding of the origin recognition complex (ORC). How ORC is positioned to sites where replication initiates is unknown, because metazoan ORC binds DNA without apparent sequence specificity. Thus, additional factors might be involved in ORC positioning. Our experiments indicate that a family member of the high-mobility group proteins, HMGA1a, can specifically target ORC to DNA. Coimmunoprecipitations and imaging studies demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 41 publications
4
102
0
1
Order By: Relevance
“…We have observed similar staining patterns for other Drosophila ORC subunits, including Orc1 and Orc2. Moreover, ORC was found in the nucleolus in human cells (31,32). These findings may indicate a potential interaction of ORC with components of the ribosome biogenesis pathway (31,33).…”
Section: Orc6 Mutant Is Defective In Dna Replication and Arrests In Bmentioning
confidence: 74%
“…We have observed similar staining patterns for other Drosophila ORC subunits, including Orc1 and Orc2. Moreover, ORC was found in the nucleolus in human cells (31,32). These findings may indicate a potential interaction of ORC with components of the ribosome biogenesis pathway (31,33).…”
Section: Orc6 Mutant Is Defective In Dna Replication and Arrests In Bmentioning
confidence: 74%
“…Human Orc6 associates with chromatin in human cell lines (27,28). Moreover, human Orc6 partially restores DNA replication when expressed in Drosophila mutant cells carrying the deletion of orc6 gene (20).…”
Section: Resultsmentioning
confidence: 99%
“…Several examples include E2F and Myb transcription factors, which interact with ORC and target it to the origin at chorion amplification locus in Drosophila (35,36). Recent studies revealed the role of HMG1A and WD repeat-containing LRWD1 proteins in targeting of ORC to the chromatin in human cells (28,37). Interestingly, human Orc6 and HMG1A proteins interact directly and may both contribute to the targeting of ORC to the sites of replication initiation and to the pre-RC assembly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] qui est essentielle pour l'assemblage du complexe pré-RC au cours de la phase G1 et l'initiation de la réplication en phase S [20,22]. Il est donc envisageable que CDT1, en coopération avec certains facteurs de transcription, puisse définir un site d'ancrage, et de régulation, de HBO1 au niveau des origines de réplication [17][18][19][20][21][22]. Il a aussi été démontré que les voies de signalisation qui régulent la transcription agissent également sur les constituants du complexe pré-RC pour contrôler la réplication [23].…”
Section: Combien D'origines Et De Classes D'origines De Réplication Dunclassified